Tantangan Dan Peluang Dalam Budidaya Tanaman Cabai - Jufriliinus Waruwu (Jurnal Ilmu Pertanian dan Perikanan, 2025)
This article aims to help us know how the growth of chili plants is. The method used in this study is to observe or conduct a survey on the growth of chili plants. Then collect and fill in the data obtained from the results of chili growth and analyze how it grows. And in this article we know how the development of chili plants is, red chili is a horticultural plant that belongs to the solanaceae family. This chili has high economic and nutritional value. In this chili plant, it is widely used or consumed in food and has nutrients such as vitamins a and c. This chili plant is also fast and it depends on the growth and nutritional value given to the chili.